546 Temporomandibular joint dysfunction syndrome – a therapeutic approach (Balneo and PRM Research Journal, 2024)
Abstract: 1) Background: Temporomandibular joint (TMJ) is responsible for vital functions like mastication, swallowing, and suction reflex and other relational functions, like talking and phonation. The etiology of temporomandibular joint disorders is multifactorial and involves subjective and objective clinical symptomatology. (2) Methods: The therapy is complex and encompasses a series of methods that interconnects various medical specialties. Bad habits and parafunction are risk factors that may initiate and exacerbate a temporomandibular joint pathology. This prospective study aimed to show the positive impact of correct multidisciplinary therapy on the complex of TMJ disorders - pain and bad oral behaviors. The therapy methods used in this study were: medical, prosthetic, orthodontic, surgical, and physiotherapy (PKT). (3) Results: The data obtained showed good results if the oral habits and TMJ disorders are treated correctly and simultaneously. (4) Conclusions: All therapeutical approaches addressed in this study had beneficial effects on the recovery of the temporomandibular joint.